A sensemaking perspective on arts sponsorship decisions. (3rd May 2016) - Daellenbach, Kate; Zander, Lena; Thirkell, Peter
Abstract : Purpose: – The purpose of this paper is to better understand the sensemaking strategies of managers involved in making decisions concerning arts sponsorship. Design/methodology/approach: – A qualitative, multiple case method is employed, using multiple informants in ten arts sponsorship decisions. Within and between case analyses were conducted and examined iteratively, along with literature to generate themes to guide future research. Findings: – This study finds art sponsorships may be seen as ambiguous, cueing sensemaking; the sensemaking strategies of senior managers involve response to pro-social cues while middle managers draw on commercial benefit cues; sensebreaking and sensegiving are part of the process; and the actors and their interpretations draw from cues in the organisational frames of reference which act as filters, giving meaning to the situations. Research limitations/implications: – This study presents a novel perspective on these decisions, focusing on the micro-level actions and interpretations of actors. It extends current understanding of sponsorship decision making, contributing to a perspective of managers responding to cues, interacting and making sense of their decisions. Practical implications: – For arts managers, this perspective provides understanding of how managers (potential sponsors) respond to multiple cues, interpret and rationalise arts sponsorships. For corporate managers, insights reveal differences in sensemaking between hierarchical levels, and the role of interaction, and organisational frames of reference. Originality/value: – This study is unique in its approach to understanding these decisions in terms of sensemaking, through the use of multiple informants and multiple case studies.